Analysis of the Pronunciation of French Sounds of the Indonesian Minister of Foreign Affairs: A Phonological Study - Atha Zamrain Husein; Bernadus Wahyudi Joko Santoso; Siti Ayu Masthuroh (Journal of Social Research, 2026)
French pronunciation accuracy is an important aspect of international communication, particularly for diplomats and state officials who use French as a language of diplomacy. Differences between Indonesian and French phonological systems may cause pronunciation interference, affecting the clarity and professionalism of spoken messages. This study aims to identify and describe the types of French pronunciation errors produced by the Indonesian Minister of Foreign Affairs in a public speech. This research employed a qualitative descriptive method. The data were obtained from a French-language speech video uploaded on YouTube and analyzed through phonological transcription using the International Phonetic Alphabet (IPA) to compare the actual pronunciation with the standard French pronunciation. The results indicate eight pronunciation errors involving four major patterns: addition of final consonants, vowel substitution, sound deletion, and inappropriate nasalization. The findings show that the errors are mainly caused by Indonesian phonological interference and the tendency to pronounce French words based on their written forms. Several errors, such as accord pronounced with an additional final consonant, dans with an unnecessary [s] sound, and Indonésie with incorrect nasal vowel realization, demonstrate difficulties in mastering French phonological rules. These errors may influence intelligibility and semantic accuracy in diplomatic communication. In conclusion, mastery of French vocabulary alone is insufficient; effective diplomatic communication requires specific pronunciation training focusing on French phonological features, particularly silent consonants, nasal vowels, schwa, and grapheme-to-phoneme correspondence.